ANALISIS FAKTOR DALAM UPAYA PENINGKATAN PRODUKTIVITAS TENAGA KERJA WANITA TANI TERHADAP USAHATANI CABAI RAWIT DI PAOK PAMPANG, LOMBOK TIMUR - Hidayanti, Anna Apriana; Usman, Abdullah; Tanaya, I Gusti Lanang Parta; Mandalika, Eka Nurminda Dewi (AGROTEKSOS, 2023)
Cayenne pepper plants are very suitable in areas that have high soil fertility, one of which is in the Rinjani Geopark Area. East Lombok Regency is one of the cayenne pepper commodity producing areas in NTB Province. Cayenne pepper farming is one of the livelihoods of the local population, especially the farm women's labor, the productivity of farm women's labor can be a source of competitive advantage of cayenne pepper farming, the higher the productivity of farm women's labor, the higher the production of cayenne pepper in East Lombok Regency so that the importance of measuring the increase in productivity of farm women's labor based on the variables obtained will be measured which variables have the most significant influence and will be seen the correlation value to the productivity of farm women's labor. Respondents used in this study were female workers who worked on chili farms in Paok Pampang village. Data collection using survey techniques by conducting interviews using questionnaires to 35 respondents. Then to analyze the factors that affect the productivity of women's labor on the cayenne pepper farm in Paok Pampang village, Sukamulia sub-district, East Lombok with reference to the variables that affect the labor time of women farmers.